2023
DOI: 10.3390/agronomy13051208
|View full text |Cite
|
Sign up to set email alerts
|

Various Population Structures of Cryphonectria parasitica in Cáceres (Spain) Determine the Feasibility of the Biological Control of Chestnut Blight with Hypovirulent Strains

Abstract: Chestnut blight, caused by Cryphonectria parasitica, is a severe disease that may be biologically controlled by the use of hypovirulent strains, but the diversity of the pathogen population affects biocontrol feasibility. Villuercas–Ibores–Jara, the Jerte Valley and La Vera are the main chestnut production districts in Cáceres (central-western Spain). The purpose of this study is to determine the Vegetative Compatibility Groups (VCGs) and mating types in these districts and to identify hypovirulent isolates to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…2) C. parasitica has been introduced in one of the neighboring regions and, from there, has arrived in Cantabria (or vice versa). In contrast, a study from Southern Spain showed that EU-1 was not the main VC type and made up only 6.6% of total isolates (Rodrıǵuez-Molina et al, 2023). Therefore, the Cantabrian populations appeared similar to other North Spanish populations but not the Southern populations.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…2) C. parasitica has been introduced in one of the neighboring regions and, from there, has arrived in Cantabria (or vice versa). In contrast, a study from Southern Spain showed that EU-1 was not the main VC type and made up only 6.6% of total isolates (Rodrıǵuez-Molina et al, 2023). Therefore, the Cantabrian populations appeared similar to other North Spanish populations but not the Southern populations.…”
Section: Discussionmentioning
confidence: 76%
“…Since the genetic diversity of the fungus is not very high in Europe, biocontrol still seems a viable option. For example, both mating types were found in Southern Spain also, but they were detected in different locations, which means sexual reproduction among them is unlikely (Rodrıǵuez-Molina et al, 2023). Nevertheless, increasing genetic diversity could make biocontrol less efficient in European populations with high genetic diversity, such as Italy, France, and Switzerland.…”
Section: Discussionmentioning
confidence: 99%
“…Planting stock, timber, and bark are pathways of long-distance dispersal [ 5 ]. This pathogen is considered for its detrimental impact on forestry and agricultural orchards for nut production [ 6 ] and is a protected-zone quarantine pest in the EU according to the Commission Implementing Regulation 2019/2072.…”
Section: Introductionmentioning
confidence: 99%